A comparison of the effects of plyometric training and ladder drills on the agility of basketball players - Andi Herdinawaty Heril; Fredrik Alfrets Makadada; Fentje Welliam Langitan; Nancy Sylvia Bawiling; Rendi Alfani; Mulham Adinda Putra; Yusril Saromeng; Muh Khafid Ansori (Departement of Sports Coaching, Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2026)
Optimal physical development supports match performance and training. However, training programs designed for physical development are often ineffective. Therefore, this study aims to determine the effectiveness of plyometric training and ladder drills on the agility of basketball players and to compare the effects of these two training methods on agility. This study was a quantitative study with an experimental design. The study population consisted of 20 basketball players from Bone Regency. The sampling technique used was total sampling. The research instrument was the Arrowhead Agility Test. Data analysis used paired t-tests and independent t-tests. The results of the data normality test showed a significance value greater than 0.05, indicating that the data were normally distributed. Both plyometric training and ladder drills significantly improved the agility of basketball athletes, and there were differences between the two training methods. The research findings indicate that both plyometric training and ladder drills significantly improved the agility performance of basketball athletes. Both methods are equally effective in improving agility. These results highlight that plyometric exercises and ladder drills can be used to improve anaerobic endurance performance.